Communication Management for Young Married Teenagers to Avoid Early Divorce - Siti arbiah (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2026)
The phenomenon of early marriage in Indonesia, particularly in Barumun Tengah District, Padang Lawas Regency, is still often characterized by the practice of marlojong, which arises as a response to communication barriers within families. This condition indicates a serious problem in communication patterns between adolescents and parents, particularly those that are still hierarchical and limit the space for dialogue, thus potentially causing conflict and weakening family functions and traditional values. This study aims to analyze the communication barriers faced by adolescents who want to marry within the family and their implications for the marlojong culture. The study used a qualitative method with a phenomenological approach to explore the subjective experiences of adolescents, parents, and traditional leaders in the marital communication process. Data were collected through in-depth interviews, observation, and documentation, then analyzed thematically. The results show that communication barriers arise from hierarchical family communication patterns and unequal power relationships, thus limiting the space for dialogue among adolescents. This condition encourages marlojong as an adaptive strategy to overcome communication deadlocks. The study also found a shift in the cultural meaning of marlojong from a mechanism of customary compromise to a symbol of resistance by the younger generation to family authority. The social and cultural implications of this phenomenon are seen in the weakening of harmonious family relations and customary legitimacy. This research emphasizes the importance of dialogic family communication to maintain the sustainability of local culture.